The Effects of Vaccinium myrtillus Extract on Hamster Pial Microcirculation during Hypoperfusion-Reperfusion Injury. - Teresa Mastantuono; Noemy Starita; Daniela Sapio; Sabato Andrea D'Avanzo; Martina Di Maro; Espedita Muscariello; Marco Paterni; Antonio Colantuoni; Dominga Lapi (PLoS ONE, 2016)
INTRODUCTION:The present study was aimed to assess the in vivo hamster pial microvessel alterations due to 30 min transient bilateral common carotid artery occlusion (BCCAO) and reperfusion (60 min); moreover, the neuroprotective effects of Vaccinium myrtillus extract, containing 34.7% of anthocyanins, were investigated. MATERIALS AND METHODS:Two groups of male hamsters were used: the first fed with control diet and the other with Vaccinium myrtillus supplemented diet. Hamster pial microcirculation was visualized by fluorescence microscopy through an open cranial window. Pial arterioles were classified according to Strahler's method. RESULTS:In age-matched control diet-fed hamsters, BCCAO caused a decrease in diameter of all arterioles. At the end of reperfusion, the reduction of diameter in order 3 arterioles was by 8.4 ± 3.1%, 10.8 ± 2.3% and 12.1 ± 1.1% of baseline in the 2, 4 and 6 month control diet-fed hamsters, respectively. Microvascular permeability and leukocyte adhesion were markedly enhanced, while perfused capillary length (PCL) decreased. The response to acetylcholine and papaverine topical application was impaired; 2'-7'-dichlorofluoresceine-diacetate assay demonstrated a significant ROS production. At the end of BCCAO, in age-matched Vaccinium myrtillussupplemented diet-fed hamsters, the arteriolar diameter did not significantly change compared to baseline. After 60 min reperfusion, order 3 arterioles dilated by 9.3 ± 2.4%, 10.6 ± 3.1% and 11.8 ± 2.7% of baseline in the 2, 4 and 6 month Vaccinium myrtillus supplemented diet-fed hamsters, respectively. Microvascular leakage and leukocyte adhesion were significantly reduced in all groups according to the time-dependent treatment, when compared with the age-matched control diet-fed hamsters. Similarly, the reduction in PCL was progressively prevented. Finally, the response to acetylcholine and papaverine topical application was preserved and there was no significant increase in ROS production in all groups. CONCLUSIONS:In conclusion, Vaccinium myrtillusextract protected pial microcirculation during hypoperfusion-reperfusion, preventing vasoconstriction, microvascular permeability, leukocyte adhesion, reduction in PCL and preserving the endothelium function.